Bell test of quantum entanglement in attosecond photoionization - Ruberti,M; Averbukh,V; Mintert,F (Physical Review X, 2024)
Attosecond physics enables the study of ultrafast coherent electron dynamics in matter upon photoexcitation and photoionization, revealing spectacular effects such as hole migration and coherentAuger dynamics in molecules. In the photoionization scenario, there has been a strong focus onprobing the physical manifestations of internal quantum coherence within the individual parent ionand photoelectron systems. However, quantum correlations between these two subsystems emergingfrom attosecond photoionization events have thus far remained much more elusive. In this work, wedesign theoretically and model numerically a direct probe of quantum entanglement in attosecondphotoionization in the form of a Bell test. We simulate from first principles a Bell test protocolfor the case of noble gas atoms photoionized by ultrashort, circularly polarized infrared laser pulsesin the strong-field regime predicting robust violation of the Bell inequality. This theoretical resultpaves the way for the direct observation of entanglement in the context of ultrafast photoionizationof many-electron systems. Our work provides a novel perspective on attosecond physics directedtoward the detection of quantum correlations between systems born during attosecond photoionization and unraveling the signatures of entanglement in ultrafast coherent molecular dynamics,including in the chemical decomposition pathways of molecular ions.